Actualization of Luqman al-Hakim’s Educational Values in Strengthening Children’s Digital Character in the Family - Yahanan Yahanan; Dewi Sri Wahyuniarti; Rahmad Fadhli; Muhamad Tasun; Siti Murtafiah; Rimma Irawani Pardede; Azhar Azmi Manurung; Syifa Zulfi (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
The expansion of digital technology has broadened children’s learning and social environments while creating challenges related to weak self-control, inappropriate content, declining communication ethics, and increasing digital validation seeking. These conditions require families not only to supervise children’s use of digital devices but also to develop their digital character through religious values. This study examines family education values in Surah Luqman verses 12–19, constructs their relevance to children’s digital character, and formulates their application within the family. It employed qualitative library research. Primary data were limited to Surah Luqman verses 12–19, Tafsir Al-Mishbah, and Tafsir Al-Azhar, while secondary data comprised relevant hadith, Islamic education books, journal articles, and institutional reports. Data were collected through documentation and analyzed using content analysis. The novelty lies in systematically transforming Luqman al-Hakim’s educational values into dimensions of children’s digital character in the family context. The findings show that monotheism strengthens digital integrity, gratitude fosters moderation, respect for parents promotes responsible compliance, prayer develops time discipline, enjoining good and preventing wrongdoing encourages critical responses to content, patience supports emotional regulation, humility reduces validation seeking, and ethical communication guides digital interaction. These values can be actualized through dialogical communication, parental role modeling, habituation, family agreements on device use, active content mediation, and gradual autonomy. Digital character is thus a contextual expression of moral education that guides children to use technology faithfully, ethically, safely, and responsibly.